WHO Model Formulary 2008. - Organization, World Health (World Health Organization, 2009)
Since its first publication in 2002, the WHO Model Formulary has become an indispensable source of independent information on essential medicines for pharmaceutical policy-makers and prescribers worldwide. The Model Formulary is the authoritative guide on how to make effective use of the medicines on the WHO Model List of Essential Medicines, so improving patient safety, and limiting unnecessary medical spending. For each medicine the Model Formulary provides information on use, dosage, adverse effects, contraindications and warnings, supplemented by guidance on selecting the right medicine fo.